Preserving Humorous Effects in a Target Language: Challenges in Translating Culturally Loaded Expressions - Rizky Lutviana; Siti Mafulah (Pascasarjana UM, 2017)
Abstract: Translating humorous discourse presents a big challenge for the translators, frequently although the intended meaning is transferred; the humorous effect may be lost due to different cultural terminologies. This research aims to unveil the challenge to translate the cultural specific words that contributed to the funny effect in a Diary of a Wimpy Kid series graphic novel. The first volume of the novel was chosen as the data source. The data were analyzed using Vandaele humor translation theory. The culturally loaded expressions words found include the words from the three foreign cultural words categories including material culture (24%), social culture (55%), and gestures and habits (21%). The challenges in preserving humorous effect dealt with the the choice of words/terminologies that could be understood by most readers, the connotative words that are full of intepretations, and the movements that were expressed in onomatopoeic words. It is suggested that the translator should develop the sense of humor and it is also important to consider the readers’ sense of humor. Key Words: humor translation, culture, graphic novelAbstrak: Menerjemahkan wacana humoris menyajikan tantangan besar bagi para penerjemah, seringkali, meskipun makna yang dimaksudkan ditransfer; efek lucu mungkin hilang karena terminologi budaya yang berbeda. Penelitian ini bertujuan untuk mengungkap tantangan dalam menerjemahkan kata-kata dalam budaya tertentu yang berkontribusi pada efek lucu dalam serial novel grafis Diary of a Wimpy Kid. Volume pertama dari novel ini dipilih sebagai sumber data. Data dianalisis dengan menggunakan teori terjemahan humor Vandaele. Ekspresi kata-kata yang sarat budaya yang ditemukan termasuk kata-kata dari tiga kata kategori budaya asing termasuk materi budaya (24%), sosial budaya (55%), dan gerak tubuh dan kebiasaan (21%). Tantangan dalam mempertahankan efek lucu dilakukan dengan menggunakan pilihan kata-kata atau istilah yang dapat dipahami oleh sebagian besar pembaca, kata-kata konotatif yang memiliki interpretasi banyak, dan gerakan yang diungkapkan dalam kata-kata onomatope. Disarankan bahwa penerjemah harus mengembangkan rasa humor dan juga penting untuk mempertimbangkan perasaan humor pembaca.Kata kunci: lelucon terjemahan, budaya, novel grafis